Extended-wavelength InGaAsSb infrared unipolar barrier detectors - Hao, Hongyue; Wang, Guowei; Han, Xi; Jiang, Dongwei; Sun, Yaoyao; Guo, Chunyan; Xiang, Wei; Xu, Yingqiang; Niu, Zhichuan (AIP advances, 2018)
We presented an extended-wavelength InGaAsSb infrared unipolar barrier detector working at room temperature. The detector with GaSb lattice-matched InGaAsSb absorb layer and AlGaAsSb unipolar barrier can achieve high material quality and low dark current. The dark current density was 2.29×10-5 A/cm2 at 0 bias at 77K. At room temperature the dark current at 0 bias was 4×10-3 A/cm2 and the R0A is high to 44 Ω · cm2. We fabricated the cone arrays in the InGaAsSb absorb layer to reduce the reflection of the radiation and extend the spectrum response to visible area. The extended-wavelength detector had the response from the wavelength of 0.4 μm. Further experiment showed the cone arrays also reduced the dark current of the detector at room temperature.